2017
DOI: 10.1007/s13340-017-0335-x
|View full text |Cite
|
Sign up to set email alerts
|

Impact of glycemic variability on the levels of endothelial progenitor cells in patients with type 1 diabetes

Abstract: Objective A reduction in endothelial progenitor cell (EPC) count is considered to correlate with cumulative cardiovascular risk factors including hyperglycemia. This study was conducted to elucidate the influence of glycemic variability on EPC count in patients with diabetes. Methods In study 1, we examined the number of EPCs in 57 patients with type 1 diabetes and 43 patients with type 2 diabetes. The number of EPCs (CD34 ? , CD34 ? CD133 ? , CD34 ? CD309 ? , and CD34 ? CD133 ? CD309 ?) was counted as the num… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 30 publications
0
4
0
Order By: Relevance
“…Poor diet control, improper treatment with insulin and hypoglycemic drugs, and inadequate compliance are associated with blood glucose fluctuation during the course of T2DM [ 33 ]; thus, glucose fluctuations are difficult to avoid in patients with diabetes. Several studies have demonstrated that IHG-induced damage is more serious than CHG in vascular endothelial cells, olfactory neuroepithelial cells, retinal epithelial cells, and Schwann cells [ 15 , 21 , 38 , 44 ]. However, the effects of IHG on neuronal cells and their potential mechanisms are unknown.…”
Section: Discussionmentioning
confidence: 99%
“…Poor diet control, improper treatment with insulin and hypoglycemic drugs, and inadequate compliance are associated with blood glucose fluctuation during the course of T2DM [ 33 ]; thus, glucose fluctuations are difficult to avoid in patients with diabetes. Several studies have demonstrated that IHG-induced damage is more serious than CHG in vascular endothelial cells, olfactory neuroepithelial cells, retinal epithelial cells, and Schwann cells [ 15 , 21 , 38 , 44 ]. However, the effects of IHG on neuronal cells and their potential mechanisms are unknown.…”
Section: Discussionmentioning
confidence: 99%
“…The direct influence of IHG on EPCs has not been tested. Nonetheless, in patients with the T1D, the J-index, a GV parameter, correlated negatively with CD34 + EPC count [77]. In turn, reducing GV with continuous subcutaneous insulin infusion increased the EPC levels in subjects with T1D [78].…”
Section: Impaired Angiogenesismentioning
confidence: 92%
“…Compared with chronic sustained hyperglycemia, glucose fluctuations induce a more specific effect on oxidative stress [ 8 ]. Severe blood glucose fluctuation is known to lower the number of vascular endothelial progenitor cells [ 28 ]. Blood glucose fluctuation is also correlated with carotid intima media thickness (IMT) [ 29 ], which is an indicator of subclinical atherosclerosis.…”
Section: Discussionmentioning
confidence: 99%